Current Progress and Outlook of Nano-Based Hydrogel Dressings for Wound Healing - Xiao Zhang; Pengyu Wei; Zhengyang Yang; Yishan Liu; Kairui Yang; Yuhao Cheng; Hongwei Yao; Zhongtao Zhang (Pharmaceutics, 2022)
Wound dressing is an important tool for wound management. Designing wound dressings by combining various novel materials and drugs to optimize the peri-wound environment and promote wound healing is a novel concept. Hydrogels feature good ductility, high water content, and favorable oxygen transport, which makes them become some of the most promising materials for wound dressings. In addition, nanomaterials exhibit superior biodegradability, biocompatibility, and colloidal stability in wound healing and can play a role in promoting healing through their nanoscale properties or as carriers of other drugs. By combining the advantages of both technologies, several outstanding and efficient wound dressings have been developed. In this paper, we classify nano-based hydrogel dressings into four categories: hydrogel dressings loaded with a nanoantibacterial drug; hydrogel dressings loaded with oxygen-delivering nanomedicines; hydrogel dressings loaded with nanonucleic acid drugs; and hydrogel dressings loaded with other nanodelivered drugs. The design ideas, advantages, and challenges of these nano-based hydrogel wound dressings are reviewed and analyzed. Finally, we envisaged possible future directions for wound dressings in the context of relevant scientific and technological advances, which we hope will inform further research in wound management.